2020
DOI: 10.1080/20016689.2020.1829883
|View full text |Cite
|
Sign up to set email alerts
|

Impact of non-medical switching of prescription medications on health outcomes: an e-survey of high-volume medicare and medicaid physician providers

Abstract: Background: Non-medical switching refers to a change in a stable patient’s prescribed medication to a clinically distinct, non-generic, alternative for reasons other than poor clinical response, side-effects or non-adherence. Objective: To assess the perceptions of high-volume Medicare and/or Medicaid physician providers regarding the impact non-medical switching has on their patients’ medication-related outcomes and health-care utilization. Methods: We performed an e-survey of high-volum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Transitions from a reference biologic to a biosimilar, or from one biosimilar to another, are often the consequence of insurance mandates and/or pharmacy benefit managers implementing formulary adjustments or limitations to reduce costs [20]. Patients might also transition between products if they relocate to a new region with different drug coverage (or if they are traveling).…”
Section: Key Pointsmentioning
confidence: 99%
“…Transitions from a reference biologic to a biosimilar, or from one biosimilar to another, are often the consequence of insurance mandates and/or pharmacy benefit managers implementing formulary adjustments or limitations to reduce costs [20]. Patients might also transition between products if they relocate to a new region with different drug coverage (or if they are traveling).…”
Section: Key Pointsmentioning
confidence: 99%
“…This non-medical switching can disrupt the benefits of ongoing treatment, requiring clinicians to alter doses and injection sites to re-establish stable regimens for each patient, particularly because there are no fixed inter-product dose ratios. Such switching can also increase the potential for medical errors, adverse events, and cessation of treatment [ 230 ].…”
Section: Discussionmentioning
confidence: 99%
“…25 In a survey of US physicians published in 2019, over 80% expressed concerns regarding nonmedical switching to biosimilars and the impact such switching would have on patient care and physician practice (Figure 2). 21,[26][27][28] In a 2019 survey of 320 US rheumatologists who prescribed tumor necrosis factor-α inhibitors, a higher proportion of respondents stated that they were more likely to initiate biosimilar treatment for a biologic treatment-naive patient with rheumatoid arthritis than they were to switch to the biosimilar for a patient with rheumatoid arthritis doing well on the reference product (73% vs 35%). 21 Likewise, in a 2020 survey of 602 specialists who regularly prescribed biologic medications to their patients, physicians were more likely to prescribe a biosimilar to patients who were newly starting therapy than to patients who were already successfully established on a reference product.…”
Section: Nonmedical Switchingmentioning
confidence: 99%
“…27,57 A large majority of patients (85%) in a survey published in 2019 were concerned that biosimilars would not treat their disease as well as a reference treatment would, 85% did not want to switch to a biosimilar if their current biologic was working, and 83% were concerned that switching may cause more adverse effects (Figure 2). 21,[26][27][28] Consequently, nonmedical switching is a major concern for patients. In a survey published in 2019, 79% of patients indicated that they attempt to avoid the switch; in another survey published in 2021, 43% of patients reported accepting the switch.…”
Section: Issues Identified From Patientsmentioning
confidence: 99%